Interleukin‐17 alters the biology of many cell types involved in the genesis of psoriasis, systemic inflammation and associated comorbidities. Issue 2 (29th December 2017) - Krueger, James G.; Brunner, Patrick M.
Abstract: Psoriasis is a chronic, immune‐mediated, systemic inflammatory disease that is defined by a characteristic skin reaction produced when elevated levels of inflammatory cytokines such as interleukin (IL)‐17 alter the growth and differentiation of skin cells. The pathogenesis of comorbid conditions associated with psoriasis, including psoriatic arthritis, cardiovascular disease, obesity, metabolic syndrome, liver disorders, renal disease and depression, is also largely affected by inflammation. In this review, we examine the effect of IL‐17 on the inflammatory pathways in a variety of different cell types, including keratinocytes, as well as epithelial cells of the colon, kidney, gut and liver. Additionally, we investigate the role of IL‐17 in mediating the psoriasis‐associated comorbidities detailed above.